Evaluation of Students’ Attitudes towards E-Learning in Moroccan Higher Education Institutions: Engineering Departments as a Case Study - HANNI, Kaoutar (Revue Internationale du Chercheur, 2022)
The use of pedagogical and technological innovations in education have altered the ways in which teachers and learners can interact. E-learning as a modern form of education is increasingly adopted in higher education (HE) and has been one of the main research lines of educational technology in the last decades. In this regard, this study attempted to investigate Moroccan university students’ attitudes towards the implementation of these new technologies in engineering education. The research study was conducted using a quantitative survey. The data were collected through a paper-based questionnaire designed for 228 students from the engineering departments. The data was gathered from undergraduate engineering students from two higher education institutions at the city of Marrakech (ENSA School & EMSI School). The study findings confirmed that the participants have highly favorable attitudes towards e-learning practices. However, the survey results indicated that these participants face various factors that impede the use and implementation of such new tools.